Students’ Environmental Knowledge in India: A Survey - Shimray, Chong; Dwivedi, Ruchi (SCHOOL SCIENCE, 2023)
The alarming rate of environmental degradation, caused by human activities, poses an unprecedented threat to the survival of all living beings on Earth. In India, attempts are being made to prepare students to tackle such challenges by integrating environmental education in the curriculum, which is also mandated by the Supreme Court. This comprehensive quantitative study was conducted to examine the environmental knowledge of 1,779 Indian school students. The study took into account various factors such as the state they reside in, their location (rural or urban) and their stage of education. This study uses stage of schooling and school location (independent variables) as demographic factors. A questionnaire with close-ended questions served as the research instrument. Data analysis employed comprehensive descriptive analysis and Kruskal-Wallis’s test using SPSS software version 27. The study found notable disparities in knowledge levels among different states and education levels, students in with secondary stage (Classes 11–12) showing better performance (p < 0.01). Interestingly, no significant difference was observed based on students’ rural or urban location. The findings suggest a need for further investigation into the factors influencing environmental knowledge variations across different states in India.